Peningkatan Prestasi Belajar PAK Menggunakan Model PBL Materi 10 Perintah Allah sebagai Pedoman Hidup Pada Siswa Kelas IV SDN Dorong - Krisna Titiliana (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The problem addressed in this study is how the implementation of the Problem Based Learning (PBL) model can enhance students' learning achievement in the subject of Catholic Education, specifically focusing on the material of the 10 Commandments as a Guideline for Life for fourth-grade students at Dorong Public Elementary School. The aim of this research is to improve the learning achievement of Catholic Education regarding the 10 Commandments as a Guideline for Life, where students' learning achievement is measured through the final comprehension test results on the material of the 10 Commandments as a Guideline for Life with a target of 70% mastery. This research adopts a quantitative approach, involving numerical data. The research process encompasses planning, implementation, observation, and reflection. Data presentation is done in the form of descriptions, graphs, tables, and conclusion drawing. The research results indicate a continuous improvement in students' learning achievement across each cycle phase. In the pre-cycle phase, the average student score was 53 with a passing percentage of 17%. In cycle I, students' learning achievement began to improve with an average score of 72 and a passing percentage of 67%. Finally, in cycle II, students' learning achievement further increased, resulting in an average score of 90 and a passing percentage of 100%. Therefore, it can be concluded that students' learning achievement has shown improvement from the pre-cycle phase, cycle I, to cycle II